ANALISIS STRATEGI BERSAING PT. KAO INDONESIA PADA INDUSTRI FAST MOVING CONSUMER GOODS DI INDONESIA - , Gading Giarono ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Current condition in Indonesia FMCG industry competition becomes more intense and competitive. The number of Indonesian society needs to continue to increase causing producer race to gain market share. Manufacturers strive to create innovative product to suit customers needs. Diverse needs of these provide opportunities for FMCG companies in Indonesia to increase its revenue. The question is whether PT. Kao Indonesia is able to compete in the FMCG industry in Indonesia with a strategy that has been around now? The main purpose of this research is to evaluate the current strategy of PT. KAO Indonesia, to analize the internal environment of the company and external environment of Indonesiaâs FMCG industry, so we can get conclusion whether the companyâs strategy is still adequate to implemented in FMCG industry and give us alternative strategy to improve the companyâs competitive ability in Indonesia FMCG industry. To evaluate how well is the companyâs present strategy working, indicator such as sales increment, industry growth, until how good is the companyâs brand image is used. The internal strength and weakness analysis is used to capturing best opportunity and defends against the threat, so the company can crafting good strategy that capitalizes on companyâs resources using functional analysis (Building Blocks of Competitive Advantages). The External analysis such as economic dominant feature, Porter five forces, PESTEL analysis, analysis of industry characteristics, is used to maximize companyâs opportunity, minimize companyâs threat and increase the opportunity to win the competition in industry.